2008
DOI: 10.1007/s11606-008-0553-9
|View full text |Cite
|
Sign up to set email alerts
|

Discussing Weight with Obese Primary Care Patients: Physician and Patient Perceptions

Abstract: OBJECTIVE: To evaluate patient-provider agreement on whether weight and related behaviors were discussed during routine visits. DESIGN:Post-visit survey assessments of patients and providers. PARTICIPANTS:Obese patients make up the majority of all patients seen in primary care (PC). The patients and physicians were recruited at the time of PC visits. MEASUREMENTS AND MAIN RESULTS:Percent patient-physician agreement and patient, provider and practice characteristics associated with agreement. Patients (456) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 39 publications
2
73
0
3
Order By: Relevance
“…Our finding that few individuals with obesity make it to the end of the cascade suggests that there is significant unmet need for obesity care at the population level. Engaging with this last step is essential to gaining access to managed, effective care and can result in a myriad of treatment outcomes, including behavioral modification, pharmacotherapy, bariatric surgery, and/or referral to another care provider 17, 18, 19, 20, 21. Our findings thus highlight the need for physicians to engage in conversation about obesity treatment at routine clinical visits, even when patients are not seeking obesity care.…”
Section: Discussionmentioning
confidence: 83%
“…Our finding that few individuals with obesity make it to the end of the cascade suggests that there is significant unmet need for obesity care at the population level. Engaging with this last step is essential to gaining access to managed, effective care and can result in a myriad of treatment outcomes, including behavioral modification, pharmacotherapy, bariatric surgery, and/or referral to another care provider 17, 18, 19, 20, 21. Our findings thus highlight the need for physicians to engage in conversation about obesity treatment at routine clinical visits, even when patients are not seeking obesity care.…”
Section: Discussionmentioning
confidence: 83%
“…For example, in a study examining the degree of agreement in which weight was discussed between patients who were obese and providers, Greiner and colleagues observed that, compared to patients, providers were more likely to report discussing weight management. 35 This discrepancy highlights the importance of effective patient-provider communication and how patients and providers perceive their own and each other's communication.…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40][41] Conversely, physicians who were perceived as disrespectful and insincere were perceived by patients as being less motivating, ineffective in encouraging behavior change, and left patients feeling hopeless. 35,37 This underscores the need for implementing the clinical strategy of "motivational interviewing" to address the Institute of Medicine's aim for improving the health care delivery system through patient-centered approaches. 42 It can be inferred that physicians in the current study had similar interactions with patients.…”
Section: Discussionmentioning
confidence: 99%
“…I en studie fant man at pasientene langt sjeldnere enn legene mente at vekten ble omtalt. Mest avvikende oppfatning hadde pasienter som i liten grad hadde forsøkt å gå ned i vekt på egen hånd (22), hvilket understreker kompleksiteten ved å samtale om dette.…”
Section: Diskusjonunclassified